2019
DOI: 10.5114/fn.2019.89856
|View full text |Cite
|
Sign up to set email alerts
|

Myricitrin attenuates memory impairment in a rat model of sepsis-associated encephalopathy via the NLRP3/Bax/Bcl pathway

Abstract: Introduction: The present investigation determined the protective effect of myricitrin against sepsis-associated encephalopathy in rats. Material and methods: Sepsis was induced by cecal ligation and puncture (CLP); rats were treated with 30 or 100 mg/kg of myricitrin for 5 days prior to the induction of CLP. The effect of myricitrin was observed by determining the neurological function using the open field test and step-down inhibitory avoidance test. Cerebral oedema and the levels of inflammatory and oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several studies have demonstrated that flavonoids alleviate sepsis brain injury (Zhu et al, 2019), memory impairment (Gong et al, 2019), cognitive dysfunction (Karimian, 2020) by exerting their antioxidant and anti-inflammatory functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that flavonoids alleviate sepsis brain injury (Zhu et al, 2019), memory impairment (Gong et al, 2019), cognitive dysfunction (Karimian, 2020) by exerting their antioxidant and anti-inflammatory functions.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study is to investigate the pathogenesis of SAE and look for effective prophylactic drugs aiming to provide early clinical intervention for SAE patients to treat brain dysfunction, thereby reducing sepsis mortality and improving the quality of life of SAE patients. Several studies have demonstrated that flavonoids alleviate sepsis brain injury ( Zhu et al, 2019 ), memory impairment ( Gong et al, 2019 ), cognitive dysfunction ( Karimian, 2020 ) by exerting their antioxidant and anti-inflammatory functions. As a member of the flavonoids family, malvidin alleviates inflammation and oxidative stress in several LPS-mediated injury models ( Bastin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gram-negative sepsis, LPS induced activation of NF-κB, which translocated to the nucleus where it promotes transcription of inflammatory mediators, including COX-2 ( 89 ). In the brain tissues of the CLP-induced mice, the expression of NF-κB was enhanced ( 90 ). The study showed that exogenous SCFAs, especially butyrate, can block the activation of NF-B in diabetic glomerulonephritis mice ( 91 ) and Usami, M. et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that myricetin could alleviate intestinal ischemia-reperfusion induced injury through attenuating inflammatory responses and oxidative stress ( Sun Y et al, 2018 ). In addition, myricetin could exert a protective effect on sepsis-associated encephalopathy through modulating inflammasome and apoptotic signaling ( Gong et al, 2019 ). However, there is a lack of research on myricetin in HIE.…”
Section: Introductionmentioning
confidence: 99%